The Sing Beling Sing Nganten Tradition: Gender Inequality and Fertility Pressures in Balinese Culture - Ismail, Habib (HUMANISMA : Journal of Gender Studies, 2025)
The Sing Beling Sing Nganten tradition in Bali is a cultural practice requiring women to prove their fertility before marriage. This tradition reflects deeply ingrained social norms and contributes to gender inequality within Balinese society. This study analyzes the tradition through the theoretical lenses of Lev Vygotsky’s sociocultural theory, Claude Lévi-Strauss’s structuralism, Kate Millett’s structuralist feminism, and Kimberlé Crenshaw’s intersectionality. Findings reveal that these cultural norms are passed down through social interactions and reinforced within traditional structures that prioritize male lineage continuity. Women are associated with nature and reproductive functions, while men serve as decision-makers within the social system. Moreover, women from lower socioeconomic backgrounds face greater pressure compared to those with access to education and economic resources. The social implications of this practice include stigma against women who fail to prove their fertility before marriage, significantly affecting their psychological well-being. Legally, there are no specific regulations protecting women from social pressure imposed by such cultural norms. Therefore, systemic changes are required, including legal reforms, women's economic empowerment, and public education to raise awareness of women's rights.